The Future Direction of Pesantren's Research: A Bibliometric Analysis - Mustofa, Mahmud Yunus; Mas'ud, Abdurrahman; Elizabeth, Misbah Zulfa (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
Academics have not quantified the quantity and quality of research conducted on pesantren (Islamic boarding school), particularly concerning the development of digital technology. Indeed, the current pesantren trend has accelerated as a response to the development of online media. This article will analyze emerging research trends, mentor academics involved in pesantren’s research, and direct researchers. Additionally, this article discusses the most influential authors and journals in the area. The research aims to evaluate pesantren's research trends indexed in Scopus using bibliometric analysis software Publish or Perish and VOS Viewer. The study discovered that pesantren's research has shifted during the last decade. According to the data, scholars continue to study pesantren's research themes infrequently, as indicated by the indexation of only 61 publications by Scopus. The majority of researchers use a conventional approach to pesantren. As such, it is critical to conduct future research on the relationship between pesantren and the advancement of digital technology. Specifically, in the form of Kiai (teacher) or santri-based learning (student-based learning) models and the process of pesantren adaptation, as indicated by the establishment of numerous pesantren media platforms as centers for religious knowledge production and dissemination. Thus, pesantren will keep being the source of religious knowledge by adapting to tradition and technology.